Utilization of a MAB for BRAF(V600E) detection in papillary thyroid carcinoma - Bullock, M; O'Neill, C; Chou, A; Clarkson, A; Dodds, T; Toon, C; Sywak, M; Sidhu, S B; Delbridge, L W; Robinson, B G; Learoyd, D L; Capper, D; et al. (Endocrine-related cancer, 2012)
Identification of BRAF(V600E) in thyroid neoplasia may be useful because it is specific for malignancy, connotes a worse prognosis, and is the target of novel therapies currently under investigation. Sanger sequencing is the 'gold standard' for mutation detection but is subject to sampling error and requires resources beyond many diagnostic pathology laboratories. In this study, we compared immunohistochemistry (IHC) using a BRAF(V600E) mutation-specific MAB to Sanger sequencing on DNA from formalin-fixed paraffin-embedded tissue, in a well-characterized cohort of 101 papillary thyroid carcinoma (PTC) patients. For all cases, an IHC result was available; however, five cases failed Sanger sequencing. Of the 96 cases with molecular data, 68 (71%) were BRAF(V600E) positive by IHC and 59 (61%) were BRAF(V600E) positive by sequencing. Eleven cases were discordant. One case was negative by IHC and initially positive by sequencing. Repeat sequencing of that sample and sequencing of a macrodissected sample were negative for BRAF(V600E). Of ten cases positive by IHC but negative by sequencing on whole sections, repeat sequencing on macrodissected tissue confirmed the IHC result in seven cases (suggesting that these were false negatives of sequencing on whole sections). In three cases, repeat sequencing on recut tissue remained negative (including using massive parallel sequencing), but these cases demonstrated relatively low neoplastic cellularity. We conclude that IHC for BRAF(V600E) is more sensitive and specific than Sanger sequencing in the routine diagnostic setting and may represent the new gold standard for detection of BRAF(V600E) mutation in PTC.